Grip force makes wrist joint position sense worse - Li, Lin; Li, Shuwang (Frontiers in Human Neuroscience, 2023)
The purpose of this study was to investigate how grip force affects wrist joint position sense. Twenty-two healthy participants (11 men and 11 women) underwent an ipsilateral wrist joint reposition test at 2 distinct grip forces (0 and 15% of maximal voluntary isometric contraction (MVIC)) and 6 different wrist positions (pronation 24°, supination 24°, radial deviation 16°, ulnar deviation 16°, extension 32°, and flexion 32°). The findings demonstrated significantly elevated absolute error values at 15% MVIC (3.8 ± 0.3°) than at 0% MVIC grip force (3.1 ± 0.2°, t (20) = 2.303, P = 0.032). These findings demonstrated that there was significantly worse proprioceptive accuracy at 15% MVIC than at 0% MVIC grip force. These results may contribute to a better comprehension of the mechanisms underlying wrist joint injuries, the development of preventative measures to lower the risk of injuries, and the best possible design of engineering or rehabilitation devices.